Intersections of two isiZulu genderlects and the construction of ’skesana’ identities - Msibi, Thabo; Rudwick, Stephanie (Stellenbosch Papers in Linguistics Plus, 2015)
Drawing on Youdell’s (2000, 2005, 2006) work on identity formation, we examine in this article multiple performances of gender identities in relation to a particular language use among African men who engage in same-sex relations. Based on semi-ethnographic research and in-depth interviews with African men who are isiNgqumo speakers in the Durban metropolitan area in KwaZulu-Natal, this article portrays the intersectional nature of two genderlects. The isiNgqumo lexicon is characterised largely by what Zulu speakers refer to as “deep” lexicon, and a closer examination reveals that a substantial number of lexical items are drawn from the isiHlonipho variety of Zulu, also termed “isiHlonipho Sabafazi” (‘women’s language of respect’). Hlonipha (lit. ‘respect’) social actions and language use are representative of showing submissiveness towards males and other people who are considered superiors. On the basis of the experiences of men who engage in same-sex relations and who self-identify as skesana, we argue that an isiNgqumo variety that draws from the isiHlonipho lexicon represents a linguistic variety that is linked to a heteronormative and patriarchal cultural system which renders femininity an inferior subject position. Within this gendered order, certain linguistic expressions of isiNgqumo can create tension-riddled identity categories and allow for complex positioning for skesanas, many of whom draw on heteronormative and heteropoleric categories in the construction of their sexual and gender identities.